Zimbabwe to phase out DDT - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1991)
DDT is to be phased out of the anti-tsetse campaign in Zimbabwe: environmentalists have found traces of the chemical, and shell thinning, in the eggs of the fish eagle population of Lake Kariba. Preliminary results of surveys, carried out by...